2012
DOI: 10.1038/aja.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-based Survivin shRNA and GRIM-19 carried by attenuated Salmonella suppresses tumor cell growth

Abstract: Persistent activation of Survivin and its overexpression contribute to the formation, progression and metastasis of several different tumor types. Therefore, Survivin is an ideal target for RNA interference mediated-growth inhibition. Blockade of Survivin using specific short hairpin RNAs (shRNA) can significantly reduce prostate tumor growth. RNA interference does not fully ablate target gene expression, owing to the idiosyncrasies associated with shRNAs and their targets. To enhance the therapeutic efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Activated STAT3 induces the expression of a number of cellular proto-oncogenes, including c-myc, c-fos and c-met, as well as cell cycle regulating proteins such as cyclin D1 and cyclin B1, which are all known to promote tumor growth. Grim-19 directly interacts with STAT3, inhibiting its gene function through Grim-19-depentment inhibitory and stimulatory pathways (34,35). In this study, STAT3 and c-myc were upregulated, and Grim-19 downregulated, indicating that atrazine may upregulate STAT3 by downregulating Grim-19, promoting RM1 cell proliferation.…”
Section: Discussionmentioning
confidence: 65%
“…Activated STAT3 induces the expression of a number of cellular proto-oncogenes, including c-myc, c-fos and c-met, as well as cell cycle regulating proteins such as cyclin D1 and cyclin B1, which are all known to promote tumor growth. Grim-19 directly interacts with STAT3, inhibiting its gene function through Grim-19-depentment inhibitory and stimulatory pathways (34,35). In this study, STAT3 and c-myc were upregulated, and Grim-19 downregulated, indicating that atrazine may upregulate STAT3 by downregulating Grim-19, promoting RM1 cell proliferation.…”
Section: Discussionmentioning
confidence: 65%
“…Salmonella typhimurium, a type of facultative anaerobic Gram-negative bacteria, can selectively accumulate in solid tumors because of the existence of hypoxic areas within solid tumors (22). Attenuated Salmonella phoPphoQ was used in the current study as a GRIM-19-expressing plasmid carrier because of its potent tumor-targeting ability, low toxicity, and ability to efficiently express exogenous gene products (23). Several studies have indicated that GRIM-19 expressing plasmids in phoPphoQ Salmonella can target solid tumors and be released into implanted tumor cells to successfully over-express GRIM-19 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Acute inflammatory reactions to bacterial presence in tumor microenvironment resulted in tumor lysis (see [154] for a review). GRIM-19 was upregulated during anti-bacterial responses and tumor lysis could be enhanced when such bacteria delivered GRIM-19 expression plasmid to the tumor [155]. However, GRIM-19 was not upregulated in chronic inflammatory conditions like arthritis [156] and IBD [36].…”
Section: Loss Of Grim-19 Increases Susceptibility To Tumor Developmentmentioning
confidence: 99%